Mistagogia: participação no mistério da fé - Lelo, Antonio Francisco (Revista Eclesiástica Brasileira, 2005)
Em busca de uma metodologia adequada para o estudo e revigoramento da participação dos fiéis na liturgia desponta a mistagogia. A teologia sacramental elaborada pelos Padres a partir da celebração litúrgica apresenta o acontecimento sacramental à luz da tipologia bíblica e com uma linguagem que faz justiça à transformação ontológica realizada naquele que recebeu a luz dos sacramentos. A interação entre fé celebrada e vivência do mistério (fé e vida) faz entender o evento sacramental como liturgia da vida, culto em espírito e verdade. Agora, o cristão é chamado a corresponder existencialmente ao dom de filiação com uma vida que o leva a adquirir a medida e a estatura de Cristo. Nesta trajetória, a espiritualidade litúrgica ergue-se como a fonte e o cume de toda vida cristã no tempo da Igreja. Tais elementos muito contribuem para avaliarmos a prática litúrgica de nossas celebrações. Abstract: In the search for an appropriate methodology to study and give renewed vigour to the faithful’s participation in the liturgy, mystagogy emerges as a valuable instrument. The sacramental theology elaborated by the Fathers on the basis of the liturgical celebration presents the sacramental event in the light of the biblical typology and with a type of language that does justice to the ontological transformation realized in those that received the light of the sacraments. The interaction between celebrated faith and the experience of the mystery (faith and life) makes us understand the sacramental event as liturgy of life, cultivated in spirit and truth. Now, the Christian is called to existentially repay the gift of filiation with a type of life that leads him/her to acquire the dimension and the stature of Christ. In this trajectory, liturgical spirituality rises as the source and the apex of all Christian life in the time of the Church. These elements are of great help in our evaluation of the liturgical practice in our celebrations.